ChemInform Abstract: A Missing Oxidation‐State Level in the Family of Polyoxo(azide)octadecavanadate(IV/V) Clusters: Synthesis, Structure and Antitumoural Properties of [VIV11VV7O44 (N3)]10‐ in a Sodium Containing‐3D Architecture. Issue 30 (7th July 2016) - Roubatis, Leonidas; Anastasiadis, Nikolaos C.; Paratriantafyllopoulou, Constantina; Moushi, Eleni; Tasiopoulos, Anastasios J.; Karkabounas, Spyridon Ch.; Veltsistas, Panayotis G.; Perlepes, Spyros P.; Evangelou, Angelos M.
Abstract: Dark khaki‐green crystals of [V18 Na10 O44 (N3 ) (H2 O)32 ]·H2 O are obtained from aqueous mixtures of VOSO4, NaN3, H2 O2, and NaOH (70 °C, 1 h, 35—40% yield).